Treatment resistant non-catatonic mutism in schizophrenia responding to a combination of continuation electroconvulsive therapy and neuroleptics - Sandeep Grover; Alakananda Dutt; Kaustav Chakrabarty; Vineet Kumar (Industrial Psychiatry Journal, 2012)
Non-catatonic mutism in schizophrenia has been described less frequently in literature. We describe the case of a young male who presented with non-catatonic mutism, secondary to first rank symptoms, which was refractory to adequate antipsychotic trials (quetiapine, risperidone, aripiprazole, ziprasidone, and trifluperazine) and responded to a combination of electroconvulsive therapy (ECT) and neuroleptics partially. However, when the ECT was continued in the continuation phase, the patient started speaking.